2014
DOI: 10.5755/j01.sace.7.2.7135
|View full text |Cite
|
Sign up to set email alerts
|

Recycled Aggregate Concrete as Material for Reinforced Concrete Structures

Abstract: Processing crushing concrete into coarse aggregate for the manufacturing of new concrete is one common means for achieving more environmentally friendly concrete. The use of recycled aggregate from construction and demolition waste as replacement of natural aggregate has increased in recent years in order to reduce the high consumption of natural resources by civil engineering. In the research work an experimental investigation was carried out to analyze the influence of steel fiber reinforcement on the load-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…Therefore, various fibres are used to reinforce recycled aggregate concrete to improve its mechanical properties [32][33][34][35]. Among many fibres, steel fibre is one of the most effective materials to enhance the tensile strength of recycled aggregate concrete [36][37][38]. Most studies have investigated the improvement in the mechanical properties of recycled aggregate concrete containing steel fibres by measuring the compressive, tensile and flexural strengths.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, various fibres are used to reinforce recycled aggregate concrete to improve its mechanical properties [32][33][34][35]. Among many fibres, steel fibre is one of the most effective materials to enhance the tensile strength of recycled aggregate concrete [36][37][38]. Most studies have investigated the improvement in the mechanical properties of recycled aggregate concrete containing steel fibres by measuring the compressive, tensile and flexural strengths.…”
Section: Introductionmentioning
confidence: 99%
“…Authors used various doses of recycled fine aggregates and based on the research outcome they concluded that the use of recycled fine aggregates in structural concrete has promising effect on the strength of the concrete. Authors in [12] used 100% replacement of course aggregates with coarse aggregates from demolished concrete to study the load-strain behavior of reinforced concrete beams along with the influence of steel fiber reinforcements. Based on the experimental results they observed that addition of steel fibers and recycled aggregates significantly increased the mechanical strength and fracture process in comparison to the control concrete.…”
Section: Wwwetasrcom Oad Et Al: Flexural Stress-strain Behavior Of Rc Beams Made With Partial Replacement Of Coarse …mentioning
confidence: 99%
“…Several studies have been carried out on reusing by-products and residual wastes as recycled materials. Among them, are the utilization of wastes as additive or substitute in concrete and cement mixtures [8][9][10][11][12]; as soil stabilization in geotechnical soil work; and in various stages of road construction [13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Despite this drawback, this method is able to reduce the space required for the disposal of CRT glass and thus contribute positively to environmental management. Kosior-Kazberuk and Grzywa [10] have discovered a method for producing sustainable concrete beam structures which utilize 100% recycled coarse aggregates. Ismail and Al-Hashmi [12] employed glass residues obtained from glass bottles and window glass with an optimum mix of 20% replacement to produce concrete with maximum compressive strength and bending, relative to the control concrete.…”
Section: Introductionmentioning
confidence: 99%